Penguatan Penegakan Etik Kepolisian Republik Indonesia Pada Komisi Kepolisian Nasional - Hardiansyah, Thoriq (Jurnal Konstitusi & Demokrasi, 2025)
In recent years there have been cases of abuse of authority committed by the Polri. this has a negative impact on the image of the police in the community. in handling the case also based on the law can only be carried out through the internal Polri in this case the Propam division through the Police Code of Ethics Commission (KKEP). The research method used is a qualitative method by combining data including normative, phenomena and in-depth analysis through comparison. the results of this ethical enforcement are not transparent and do not match what violators do. So that the results of this study indicate that there is a need to strengthen the authority of kompolnas as an independent institution and police partner who is directly responsible to the President to be able to supervise and enforce ethics on the police in Indonesia. The importance of the implementation of ethical supervision and enforcement in the police by strengthening the authority of kompolnas can provide transparency and increase public confidence in the Police.